Countering Hate Speech on Facebook: The Case of the Roma Minority in Slovakia - Miškolci, Jozef; Kováčová, Lucia; Rigová, Edita (Social science computer review, 2020)
This article explores hate speech against the Roma in Slovakia on Facebook between April 2016 and January 2017 and the impact of fact-checking and personal experience strategies in countering hate speech through a quasi-experimental research design. It examines how the Roma were constructed and how discussion participants reacted to our pro-Roma interventions. The research sample consisted of 60 Facebook discussions (with more than 7,500 comments) on Roma-related topics posted by the profiles of various members of the Slovak Parliament and the most popular online news media outlets. Qualitative content analysis revealed that the Roma in Facebook discussions were constructed primarily in a negative sense, as asocial criminals misusing welfare benefits. This study demonstrated that Facebook discussion participants presenting anti-Roma attitudes did not use any research evidence to support their constructions. It also demonstrated that pro-Roma comments encouraged other participants with a pro-Roma attitude to become involved.